2017
DOI: 10.1158/1538-7445.sabcs16-s3-05
|View full text |Cite
|
Sign up to set email alerts
|

Abstract S3-05: Integrated analysis of multidimensional genomic data on CALGB 40601 (Alliance), a randomized neoadjuvant phase III trial of weekly paclitaxel (T) and trastuzumab (H) with or without lapatinib (L) for HER2-positive breast cancer

Abstract: Background: RNA profiling and mutational analyses in CALGB 40601 (NCT00770809) found significant impact on pathologic complete response (pCR) rates from tumor (intrinsic subtype, p53 mutation) and microenvironmental (immune cell) features. Integrated analysis across platforms is needed to better understand the roles of these different factors with respect to response to HER2-targeted therapies. Methods: We performed a comprehensive genomic analyses on pCR, defined as no invasive tumor in the bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The Neo ALTTO (ClinicalTrials.gov identifier NCT00553358) 133 and the German Breast Group trials 134 demonstrated that distinct genes or pathway‐level DNA alterations are predictive of responses to HER2‐directed therapy. In CALGB 40601, integrated DNA and RNA analyses concluded that there was an independent association between copy number alterations and pCR rates when the investigators accounted for the RNA expression signature subtype 135 …”
Section: Challenges Associated With Her2‐directed Therapymentioning
confidence: 99%
“…The Neo ALTTO (ClinicalTrials.gov identifier NCT00553358) 133 and the German Breast Group trials 134 demonstrated that distinct genes or pathway‐level DNA alterations are predictive of responses to HER2‐directed therapy. In CALGB 40601, integrated DNA and RNA analyses concluded that there was an independent association between copy number alterations and pCR rates when the investigators accounted for the RNA expression signature subtype 135 …”
Section: Challenges Associated With Her2‐directed Therapymentioning
confidence: 99%